Analysis of Architectural Needs for Passive Low-Tech Fog and Dew Collector Building Design: A Narrative Literature Review - Muhammar Khamdevi; Matius MLT (Jurnal Arsitektur TERRACOTTA, 2023)
Global warming and climate change have negative effects on life on earth. One of the consequences is a water crisis or water scarcity, both in quantity and quality. Indonesia also cannot avoid this problem. Therefore it is necessary to prepare an alternative water supply solution, one of which is from water vapor (atmospheric water), especially in the form of dew and fog. This study aimed to formulate the design requirements for passive low-tech dew and fog collector building by comparing several technologies and projects in the world that have been realized recently that have a relationship with architectural science. This research used qualitative research with a narrative literature review approach. This research produced design requirements in the form of principles and technical requirements in designing and realizing dew and fog collector building, especially in terms of function, construction, and appearance.Keywords: dew collector, fog collector, low-tech, water scarcity, architecture